Perceived value dan brand trust terhadap purchase intention dengan mediasi brand preference - Latifah, Silvi Zulia; Fikriah, Nur Laili (Journal of Management and Digital Business, 2024)
This study aims to identify the mediating role of brand preference in the relationship between perceived value, brand trust, and intent to buy. Data for this study came from a Google Forms survey that used a quantitative methodology with a descriptive focus. The study sites are the five cities in East Java—Surabaya, Sidoarjo, Jember, Malang, and Banyuwangi. The sample size was chosen using the Ferdinand method, and the sample consisted of 200 respondents. Purposive sampling was used to select the sample. An SEM based on Partial Least Square (PLS) is used to analyze the data. The study results show that perceived value and brand trust influenced purchase intention. Perceived value and brand trust influence brand preference, and brand preference influences purchase intention. Other results show that brand preference can mediate the effect of perceived value brand trust on purchase intention on Ventela Shoes products in the Shopee marketplace.